Masalah-masalah setinggan Cina di daerah Ulu Langat,Selangor pada masa darurat,1948-1960 - Wong, Siew Kuon (Monographs of the Malaysian Branch of the Royal Asiatic Society, 1999)
Essays on: The problems of Chinese squatters in the Ulu Langat District of Selangor during the emergency, 1948-1960; and History of diplomacy and trade in nineteenth century Labuan Island, Borneo.